2020
DOI: 10.1016/j.celrep.2020.107684
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Signaling Has a CXCL12-Independent Essential Role in Murine MLL-AF9-Driven Acute Myeloid Leukemia

Abstract: Highlights d In vivo CRISPR screening identifies CXCR4 as a key regulator of AML stem cells d CXCL12 expression in the bone marrow is dispensable for AML development d CXCR4 signaling protects AML cells from oxidative stress and differentiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 79 publications
0
28
0
Order By: Relevance
“…37 Recently, a murine MLL-AF9-driven AML model was used to evaluate the engraftment of leukaemia cells into mouse BM. 38 The deletion of cxcr4 in AML cells eradicated leukaemia cells in vivo, but their homing to the BM was not impaired. Furthermore, SDF-1 is dispensable for the development of leukaemia in mice.…”
Section: Cxcr4 Participates In Homing and Residence Of Aml Cells In Bmmentioning
confidence: 99%
“…37 Recently, a murine MLL-AF9-driven AML model was used to evaluate the engraftment of leukaemia cells into mouse BM. 38 The deletion of cxcr4 in AML cells eradicated leukaemia cells in vivo, but their homing to the BM was not impaired. Furthermore, SDF-1 is dispensable for the development of leukaemia in mice.…”
Section: Cxcr4 Participates In Homing and Residence Of Aml Cells In Bmmentioning
confidence: 99%
“…Recently, Ramakrishnan et al ( 150 ) demonstrated that CXCR4 alone provides sufficient signaling in the absence of CXCL12 ligation to promote the expansion and survival of murine AML cells in vivo . Therefore, if CXCR4 expression is maintained, disruption of the CXCR4/CXL12 axis alone might be insufficient to effectively sensitize leukemic cells to cytotoxic chemotherapy.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Interestingly, CXCL12 was dispensable for leukemia development, whereas CXCR4 signaling was essential for AML cells preventing their differentiation. Importantly, these data demonstrate that beyond its role in mediating crosstalk to the microenvironment, CXCR4 acts also cell-intrinsically, triggering key signaling cascades promoting and maintaining the malignant phenotype of the cell 28 . As expected, EPI-X4 impaired phosphorylation of the MAPK pathway, documented by FACS and PAMChip-based quantification of phosphorylation of members of this pathway and validated by Western blot.…”
Section: Discussionmentioning
confidence: 90%